Hubungan Mekanisme Koping dengan Tingkat Stres pada Pasien Diabetes Melitus - Yudi Akbar; Mursal Mursal; Novia Rizana; Sri Andala (Universitas Pahlawan Tuanku Tambusai, 2025)
Coping mechanisms are important factors for people with diabetes because they can provide potential benefits in emphasizing cognitive and behavioral strategies to improve health levels in the lives of people with diabetes. The purpose of this study was to determine the relationship between coping mechanisms and stress levels in patients with diabetes mellitus. This study used a correlation analytic design with a cross-sectional study method. Sampling was carried out using the total sampling technique. The measuring instruments used were the brief cope questionnaire and the perceived stress scale, and the data analysis used was univariate and bivariate. The results showed that the majority of respondents were aged 56-65 years as many as 45 respondents (44.1%), 66 respondents (35.7%) were female, 35 respondents (34.5%) had a high school education, 60 respondents (58.8%) had diabetes for 1-5 years. The majority of patient coping mechanisms were in the adaptive category, namely 75 respondents (74.5%) and the majority of stress levels were in the mild category as many as 85 respondents (84.4%), and there was a relationship between coping mechanisms and stress levels (p-value 0.001). Diabetes mellitus sufferers who are supported by good coping mechanisms will increase their hope for recovery because they can reduce stress levels and want to seek treatment regularly. It is recommended that diabetes mellitus sufferers increase their awareness and motivation in dealing with diabetes mellitus problems.